Auditory cortical neurons are recruited to encode fear signals and anxiety by neuroligin-3-mediated synapse formation - Yun Zhang; Bingchen Chen; Jiayi Li; Lei Wang; Yang Xu; Jin-Hui Wang (Translational Psychiatry)
Abstract The social stress often induces fear memory and stress-relevant phobias. Molecular and cellular mechanisms of fear memory and anxiety remain to be addressed for the exploration of therapeutic strategies for these deficits. In social defeat mice induced by the resident/intruder paradigm, we have examined how auditory cortical neurons are recruited to encode stress signals that cause fear memory and anxiety by approaches of behavioral tasks, neural tracing, electrophysiology and molecular biology. The social stress in intruder C57 mice by the attack of resident CD1 mouse causes their fear memory and anxiety-like behaviors. In addition to the interconnections between auditory and somatosensory cortices in the mice of fear memory and anxiety, auditory cortical neurons receive new synapses from the somatosensory cortex and the synapses from the medial geniculate body. These auditory cortical neurons are able to encode the stress signals including the pain stimulus to injury areas and the battle sound in a resident/intruder paradigm. Neuroligin-3 mRNA knockdown in the auditory cortex prevents the recruitment of associative memory neurons that encode fear memory and anxiety-like behaviors. Therefore, neuroligin3-mediated synapse formation is essential for the stress-induced recruitment of associative memory neurons in auditory cortices that encode stress signals, fear memory and anxiety.